2020
DOI: 10.1016/j.ophtha.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Macular Atrophy Incidence and Progression in Eyes with Neovascular Age-Related Macular Degeneration Treated with Vascular Endothelial Growth Factor Inhibitors Using a Treat-and-Extend or a Pro Re Nata Regimen

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“… 116 In a 4-year study, Spooner et al compared progression rates of macular atrophy among 264 eyes treated with anti-VEGF using either PRN or TREX regimes. 117 They found that VA gains among the TREX group were higher compared to the PRN group after 1 year of treatment (+2.7 vs +0.3 letters respectively), however these gains were lost after 4 years (+0.9 vs −0.5 letters, respectively). More long-term prospective data is needed between these two regimes.…”
Section: Anatomic Factorsmentioning
confidence: 95%
“… 116 In a 4-year study, Spooner et al compared progression rates of macular atrophy among 264 eyes treated with anti-VEGF using either PRN or TREX regimes. 117 They found that VA gains among the TREX group were higher compared to the PRN group after 1 year of treatment (+2.7 vs +0.3 letters respectively), however these gains were lost after 4 years (+0.9 vs −0.5 letters, respectively). More long-term prospective data is needed between these two regimes.…”
Section: Anatomic Factorsmentioning
confidence: 95%
“…These cumulative rates of SRFi and MA were similar to those reported elsewhere. 9 , 16 , 17 The Macular atrophy in Pro re Nata versus Treat-and-Extend (MANEX) study reported that the incidence of new atrophy lesion in consecutive naïve treated nAMD eyes receiving VEGF inhibitors was approximately 19% and 22% at 2 and 3 years of treatment, respectively. 9 In the comparison of AMD Treatments Trials (CATT), non-geographic atrophy and scar rates were estimated to be approximately 12 to 19% and 16 to 20% at 2 years, respectively, depending on the type of drug and treatment pattern.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 16 , 17 The Macular atrophy in Pro re Nata versus Treat-and-Extend (MANEX) study reported that the incidence of new atrophy lesion in consecutive naïve treated nAMD eyes receiving VEGF inhibitors was approximately 19% and 22% at 2 and 3 years of treatment, respectively. 9 In the comparison of AMD Treatments Trials (CATT), non-geographic atrophy and scar rates were estimated to be approximately 12 to 19% and 16 to 20% at 2 years, respectively, depending on the type of drug and treatment pattern. 17 , 18 The FRB registry has implemented the ICHOM classification grading of SRFi and MA to standardize the diagnosis of these features and compare outcomes between different reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean number of anti-VEGF injections in the EAGLE study at Year 1 was 5.6, an improvement on the previous routine clinical practice study, AURA (5.2 in 2 years for Italy) [ 15 ]. Despite this improvement, the mean number of injections clearly shows that patients in the EAGLE study were undertreated with respect to pivotal randomized controlled trials [ 10 12 , 16 ] and other routine clinical practice studies, particularly those adopting a proactive and customized treatment approach, with the goal of preventing disease recurrence [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%